KARAKTER DALAM TARI GAYA SURAKARTA - Silvester Pamardi; Timbul Haryono; R.M. Soedarsono; AM. Hermien Kusmayati (Institut Seni Indonesia Surakarta, 2014)
This writing is aimed at explaining characters in Surakarta style dance rooted at the palace. In Indonesiandance knowledge it is known as classic dance. Surakarta style dance has developed so long that has builtsystematized patterns of move and been fully fledged based on pakem beksa containing with many rules andtechniques of movements of palace dance. Javanese society believes that palace dance is a cultural heritagecontaining both values of guidance and entertainment as well. The concept of beauty of palace dance hasthree norms. Those are Hastakawaca, Kawaca, and Hastakawaca Gendhing. The norms show that the dancehas soul and movement such as container and content unified in inner and outer life. The masters (empu) ofJavanese dance believe that dance movement expressed through the body of dancer will produce innerattitude. Some people are able to find its philosophy at the time of dance appreciation. This paradigm can bedefined as an implementation of functional values of palace dance giving characters guidance and good soul.Identified through dance forms perspective, palace dance is a collective soul expression. In relation tomovement, palace dance expresses the soul of Javanese personality. In the sense of being a collectiveÂ expression related to customary structures, the movement of palace dances covering the whole body meansbuilding up good soul. The character of palace dances is constructed with typology, temperament, and dispositionderived from or transformation of the forms of shadow play. The forms of shadow play have physical size(typology), motion puppet play (temperament), and wanda (character) in different visual appearance for eachcharacter or role. The characters structured in the forms of dance movement serves as the values of guidancethrough appreciation towards the values of nature and the roles of motion expressing bad and good teaching.Keywords: dance, character, philosophy, aesthetic, Surakarta style